(untitled) (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
The design of an operating system (OS) plays an important role in the design of modern video game performance, responsibility and scalability. Skilled management of the OS level of resources such as CPU planning, memory allocation and I/O handling directly affects the framework, delay and total lubrication of gameplay. This article suggests how the OS architecture affects both gaming development and user experience by examining factors such as accountability, texture, fault tolerance and scalability in the multiplayer environment. This emphasizes the importance of OS functions such as process planning, thread management and compatibility with modern graphics -APIs that enable stable and merging gaming experiences. In addition, interaction between the OS-level design and play architecture is analyzed, especially distributed systems and in areas such as cloud-based games. Emerging technologies such as Virtual Reality (VR), Enhanced Reality (AR) and Massive Online Platforms are developing, the optimization of the OS design is becoming increasingly important. The study concludes that the deep understanding of the OS interns is necessary for developers to create high performance, resource-developed and reliable game applications.